Lipoproteins: When size really matters - German, J. Bruce (2006)
The field of nanoscience is extending the applications of physics, chemistry and biology into previously unapproached infinitesimal length scales. Understanding the behavior and manipulating the positions and properties of single atoms and molecules hold great potential to improve areas of science as disparate as medicine and computation, and communication and orbiting satellites. Yet, in the race to develop novel, previously unavailable nanoparticles, there is an opportunity for scientists in this field to digress and to apply their growing understanding of nanoscience and the tools of nanotechnology to one of the most pressing problems in all of human biology—diseases related to lipoproteins. Although not appreciated outside the field of lipoprotein biology, variations in the compositions, structures and properties of these nanoscale-sized, blood-borne particles are responsible for most of the variations in health, morbidity and mortality in the Western world. If the lipoproteins could be understood at the nanometer length scale with precise details of their structures and functions, scientists could understand a wide range of perplexing physiological processes and also address the dysfunctions in normal lipoprotein biology that lead to such diseases as hypercholesterolemia, heart disease, stroke and neurodegenerative diseases. Furthermore, if the capabilities of nanoscience to assemble and manipulate nanometer-sized particles could be recruited to studies of lipoproteins, these biological particles would provide a new dimension to therapeutic agents, and these natural particles could be designed to carry out many specialized beneficial tasks.